2000
DOI: 10.7863/jum.2000.19.8.565
|View full text |Cite
|
Sign up to set email alerts
|

Second trimester ultrasonography may identify 77 to 97% of fetuses with trisomy 18.

Abstract: n 1984 maternal serum screening for aneuploidy was ushered in when trisomy 18 was identified in a patient in whom the maternal serum AFP level was undetectable. 1 After making this observation, Merkatz and associates examined maternal serum from 41 women who had fetuses with aneuploidy and found that the AFP multiple of the median was lower in fetuses with aneuploidy than in control fetuses. 1 After this observation, numerous investigators reported the association between maternal serum markers and an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 23 publications
0
30
1
2
Order By: Relevance
“…[1][2][3][4] Choroid plexus cysts have elicited concern because they are visualized on prenatal ultrasound in fetuses with trisomy 21 and as many as 53% of fetuses with trisomy 18. 5,6 Usually, other abnormal ultrasound findings differentiate these chromosomal aneuploidies from an isolated CPC. [7][8][9] However, several studies have reported that an isolated CPC on prenatal ultrasound may confer a slightly higher risk of trisomy 21 3,10 and 18, 1,11,12 which becomes more significant if additional risk factors, such as advanced maternal age, are present.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Choroid plexus cysts have elicited concern because they are visualized on prenatal ultrasound in fetuses with trisomy 21 and as many as 53% of fetuses with trisomy 18. 5,6 Usually, other abnormal ultrasound findings differentiate these chromosomal aneuploidies from an isolated CPC. [7][8][9] However, several studies have reported that an isolated CPC on prenatal ultrasound may confer a slightly higher risk of trisomy 21 3,10 and 18, 1,11,12 which becomes more significant if additional risk factors, such as advanced maternal age, are present.…”
Section: Introductionmentioning
confidence: 99%
“…15 Of these, choroid plexus cysts (Fig. 5) have been the most controversial and the subject of considerable interest.…”
Section: Markersmentioning
confidence: 99%
“…They are seen in up to half of second-trimester fetuses and are often found with other anomalies. [3][4][5][6][7][8][9][10][11][12][13] In the nearly 2 decades since the initial report by Chudleigh et al, 1 a large volume of literature has been published regarding the sonographic detection of choroid plexus cysts in the second trimester. Despite this, a consensus of opinion has yet to be reached on the genetic significance and appropriate management when these cysts are detected as an isolated finding.…”
mentioning
confidence: 99%